2015
DOI: 10.1021/jacs.5b01671
|View full text |Cite
|
Sign up to set email alerts
|

Direct Aerobic Carbonylation of C(sp2)–H and C(sp3)–H Bonds through Ni/Cu Synergistic Catalysis with DMF as the Carbonyl Source

Abstract: The direct carbonylation of aromatic sp(2) and unactivated sp(3) C-H bonds of amides was achieved via nickel/copper catalysis under atmospheric O2 with the assistance of a bidentate directing group. The sp(2) C-H functionalization showed high regioselectivity and good functional group compatibility. The sp(3) C-H functionalization showed high site-selectivity by favoring the C-H bonds of α-methyl groups over those of the α-methylene, β- or γ-methyl groups. Moreover, this reaction showed a predominant preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(118 citation statements)
references
References 63 publications
1
117
0
Order By: Relevance
“…[30] Succinimide derivatives were prepared from corresponding aromatic or aliphatic amides with 10 mol-% of a Ni I salt and 20 mol-% Cu(acac) 2 in the presence of DMF under oxygen gas. For reactions of aliphatic amides, a predominant preference of functionalizing the methyl group over the methylene groups including the relatively reactive benzyl group was observed.…”
Section: Copper/nickel-catalyzed Carbonylation Of C(sp 3 )-H Bondsmentioning
confidence: 99%
“…[30] Succinimide derivatives were prepared from corresponding aromatic or aliphatic amides with 10 mol-% of a Ni I salt and 20 mol-% Cu(acac) 2 in the presence of DMF under oxygen gas. For reactions of aliphatic amides, a predominant preference of functionalizing the methyl group over the methylene groups including the relatively reactive benzyl group was observed.…”
Section: Copper/nickel-catalyzed Carbonylation Of C(sp 3 )-H Bondsmentioning
confidence: 99%
“…Ge recently reported on the Ni(II)/Cu(II)-catalyzed carbonylation of benzamides containing an 8-aminoquinoline as the directing group with DMF as the carbonyl source (Scheme 15) [42]. The presence of both a Ni and a Cu catalyst was required for the reaction to proceed.…”
Section: Carbonylation Of C(sp 2 )-H Bondsmentioning
confidence: 99%
“…Ge reported on the Ni(II)/Cu(II)-catalyzed carbonylation of C(sp 2 )-H bonds in aromatic amides containing an 8-aminoquinoline as the directing group with DMF as the carbonyl source (Scheme 15) [42]. This catalytic system was applicable to the carbonylation of C(sp 3 )-H bonds (Scheme 25) [42].…”
Section: Scheme 23mentioning
confidence: 99%
See 1 more Smart Citation
“…[8] More recently, Ge and co-workers demonstrated that the methyl group from DMF can service as a carbonyl source on nickel-catalyzed carbonylative C-H activation. [9] Based on our continual interests on carbonylation transformations, [10] here we wish to report our new finding on using the carbonyl part of DMF as the CO source for Pd/Ccarbonylative C-H activation.…”
Section: Introductionmentioning
confidence: 99%